(untitled) (Research, Society and Development, 2017)
The present study aims to identify the total municipal expenditures with drugs, correlating the expenditures with the pharmaceutical. Pharmaceutical care has receiving increasing attention from governments, institutions and professionals from around the world both by increased spending on health as the demand is growing, and the resources are finite to ensure comprehensive health care of the citizens, the study in question, used data from secondary sources for the study of government procurement with the primary purpose of a comparison between municipal expenses in the same region, the spending on drugs in a general context is about 30-40% of the health budget Nominations found in this study suggest that spending on the Pharmaceutical Assistance program whose acquisitions are the responsibility of the Ministry of Health and centralized in the EU, showed a significant increase from 2010 to 2015. We analyzed preliminarily the size of spending, not effectiveness these Software.